The Effect of Profitability, Leverage and Capital Intensity on The Effective Tax Rate On Lq45 Companies on The Indonesia Stock Exchange (IDX) For The Period 2016 – 2019 - Siti Alya Nabilla; Josua Panatap Soehaditama (ABNUS Publisher, 2023)
This study was conducted in order to find out the impact of profitability, leverage and capital intensity on the effective tax rate in LQ45 companies on the Indonesia Stock Exchange (IDX). This study uses data derived from the economic report of the LQ45 company listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 period. This study uses quantitative methods, then the data obtained will then be in the form of numbers. The results of this study are the discovery of negative and substantial profitability impacts on the effective tax rate, found negative and substantial impacts of leverage on the effective tax rate and no impact of capital intensity on the effective tax rate on LQ 45 companies on the Indonesia Stock Exchange (IDX) for the period 2016 - 2019.